Production of a Symbiotic Biopreparation (Mixture of Agave fourcroydes Lem. Pulp and PROBIOLACTIL®) for Use in Calves - Rondón, Ana J.; del Valle, Arianne; Milián, Grethel; Arteaga, Fátima G.; Rodríguez, Marlén; Valdivia, Aymara; Martínez, Marlene (Agrisost ISSN 1025-0247, 2019)
Context: Artificial calf breeding may lead to gastric disorders in animals, which are produced due to inappropriate nutritional practices.Objective: Production of a Symbiotic Biopreparate (Mixture of Agave fourcroydes Lem. Pulp and PROBIOLACTIL®) in Calves.Methods: The design and optimization of this biopreparation was based on the response surface method, with a rotating central composite experimental design 22, and two replications. Henequen pulp was used with the addition of molasses and yeast hydrolyzate, as sources of sugar and nitrogen, respectively, and PROBIOLACTIL® for supplementation of Lactobacillus salivarius. The experiment lasted 28 days, with a completely randomized design, to evaluate the effect of this additive on the productive and health indicators of Mambi de Cuba calves, at weaning and breeding.Results: Optimum values were achieved for the components of the biopreparation, which increased the production of Lactobacillus. The application of the additive improved live weight, mean daily gain, and weight gain, from the 21st day on, and its influence on health was seen through a reduction in the occurrence of diarrhea.Conclusions: The biopreparation was designed from a probiotic culture of agroindustrial residues, then enriched with highly available national components. This symbiotic biopreparation may be used as a nutritional additive in weaned calves.
Keywords: probiotics; zootechnical additives; Lactobacillus salivarius